The Effect of Art Therapy on Problem-Solving Skills, Self-Concept, and Interpersonal Relationships in Children with Separation Anxiety Disorder in Tehran - Kavoussi, Parisa; Ebrahim Moghadam, Hossein (Iranian Journal of Neurodevelopmental Disorders, 2024)
Purpose: This study aimed to enhance the skills of children with separation anxiety disorder in the areas of problem-solving, self-concept, and interpersonal relationships by examining the effectiveness of art therapy.Method: The present study employed a quasi-experimental design with a pretest-posttest and a control group. Based on Cohen’s table, the sample size was estimated to be 30 participants, who were randomly assigned to two equal groups: an experimental group (n = 15) and a control group (n = 15). Four questionnaires were used for assessment: the Child Anxiety-Related Disorders Diagnostic Questionnaire, the Heppner and Petersen Problem-Solving Inventory, the Piers-Harris Self-Concept Scale, and the Barton J. A. Interpersonal Skills Questionnaire. After entering the data into SPSS-23, a multivariate analysis of covariance (MANCOVA) was used for data analysis.Findings: The results indicate that art therapy is effective in improving problem-solving skills, self-concept, and interpersonal relationships in girls with separation anxiety disorder.Conclusion: The findings show a significant difference in posttest scores of the experimental group in all three dependent variables: problem-solving skills, self-concept, and interpersonal relationships. Each of these variables demonstrated a significant improvement in the posttest compared to the control group.